Pengembangan Media Belajar Mengajar IPA dengan Penerapan Melalui Pembelajaran Konstruktivisme Development of Learning Media to Teach IPA by Application Through Constructivity Learning - Grafika Ramadhanti Ekananda (ScienceEdu: Jurnal Pendidikan IPA, 2019)
Media is a means that can be used to convey information to students, one of which is learning constructivism. In learning. Constructivism is one of the schools of philosophy of knowledge which emphasizes that our knowledge is our own (formed) construction. At present a teacher must stimulate students so that students become more active. The learning delivered by the teacher that is theoretical will get less than optimal results. Learning media becomes interesting when it can contribute positively to learning outcomes. because every subject that is usually considered difficult to understand becomes very interesting, the learning media also has an aesthetic appeal so that an attractive and eye-catching display will motivate users to be involved in the learning process. The results of the study showed that the application of learning media in the activities of explaining science lessons in class could optimize students' learning motivation.